COMMUNICATION AND MUSEUMS: MUSEUMS AS A PLACE OF DISCOURSE - Ka Tat Nixon Chen (The Indonesian Journal of Communication Studies, 2014)
Museums are to communicate their meaning to societies through their discourse.  Through the discourse, museums are to convey certain values, ideas or truths to societies.  The discourse of a museum embraces a power which can generate or instill a common sense and reinforce or give new insight to museum visitors.  Up to a point, the discourse of a museum can be in agreement or in contradiction with the existing knowledge and beliefs of visitors.  To understand museums is to understand the discourse of museums.  No two museums are the same.  It is the discourse of a museum that makes museums different and meaningful to societies.  No discourse is neutral.  “Museums are invention of men….They exist for the things we put in them (Silver, cited in Weil, 1990, p. xiv).”  The discourse of museums is subjected to the arrangement of mankind.  This paper is to look into the way museums garnish their objects and functions with specific concepts and assumptions to impart into the understanding of museum visitors of the discourses of museums.  Museums as a place of discourse are to influence the visitors’ perception and understanding of the world at large.